1990
DOI: 10.1111/j.1464-5491.1990.tb01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid and Other Organ‐specific Antibodies in Saudi Arab Diabetic and Normal Children

Abstract: Sera from 162 Saudi Arab children were examined for autoantibodies to thyroid microsomes, thyroglobulin pancreatic islet cells, gastric parietal cells, and adrenocortical cells. The subjects included a control group (n = 76) and 86 children below 14 years with Type 1 diabetes. Antithyroid antibodies were detected in 8.1% of the diabetic group and in none of the control group. Parietal cell antibodies were found in 9.3% of the diabetic group and 4.4% of the control group; 14.6% of diabetic children and 2.2% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…However, it is similar to the prevalence found in Iranian children (39.6s%) [ 17 ]. Our results are considerably higher than those found in either Libyan [ 6 ], Jordanian [ 9 ], Saudi Arabian [ 13 ] and Sudanese children [ 14 ].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…However, it is similar to the prevalence found in Iranian children (39.6s%) [ 17 ]. Our results are considerably higher than those found in either Libyan [ 6 ], Jordanian [ 9 ], Saudi Arabian [ 13 ] and Sudanese children [ 14 ].…”
Section: Discussioncontrasting
confidence: 88%
“…The age-standardized incidence in children aged 0–14 years in Kuwait between 1992 and 1999 was reported as 20.9/100,000 [ 10 ]. Studies on the prevalence of Th-AA in Arab children with type 1 diabetes are scarce [ 6 , 13 , 14 ], and longitudinal studies assessing the risk of Th-AA are lacking. Therefore, we undertook this study to (1) investigate the prevalence and natural history of Th-AA among Arab children and adolescents with type 1 diabetes in Kuwait and (2) determine the clinical significance of the detection of TAA as a marker for autoimmune thyroid disease in children with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA haplotype of class II DQB1 0201/0202 -DR104 was found to be associated with type 1 diabetes in Saudi patients whereas the presence of DPB1-0401 is protective against the disease, suggesting that the haplotype DR4 confers risk of the disease in the same way it does in other population groups. 19 Immune markers for endocrine disease were assessed in a group of diabetic children and normal controls by Abdullah et al 20 Of the Saudi diabetic children, 14.6% were positive for islet cell antibodies vs 2.2% of the normal controls. Of interest, 56% of those tested at the onset of diabetes were positive for those antibodies.…”
Section: Specific Diabetes Syndromesmentioning
confidence: 99%
“…In two recent studies from Sudan [22, 23], the reported prevalence of ICA in children and young adults with IDDIM was 42 and 63% at diagnosis. These frequencies were much higher than reported in Africans and black Americans [16, 24, 25], as well as from the Arab World [26].…”
Section: Discussionmentioning
confidence: 58%